Classification Systems of Secondary Active Transporters. (March 2017) - Perland, Emelie; Fredriksson, Robert
Abstract : Membrane-bound solute carrier (SLC) transporter proteins are vital to the human body, as they sustain homeostasis by moving soluble molecule as nutrients, drugs, and waste across lipid membranes. Of the 430 identified secondary active transporters in humans, 30% are still orphans, and systematic research has been requested to elaborate on their possible involvement in diseases and their potential as drug targets. To enable this, the various classification systems in use must be understood and used correctly. In this review, we describe how various classification systems for human SLCs are constructed, and how they overlap and differ. To facilitate communication between researchers and to avoid ambiguities, everyone must clearly state which classification system they are referring to when writing scientific articles. Trends: SLCs are crucial for maintaining homeostasis within the body as they control molecular trafficking across cellular lipid membranes. SLCs are also implicated in several diseases and they constitute possible drug targets. There are fewer publications on SLCs than on other protein families, showing that the SLC family is understudied. Systematic research has been requested within the field. There are several SLC classification systems in use, to facilitate efficient communication between researchers. However, the many classification systems result in ambiguities and misunderstandings. Understanding the different classification systems in use today aids a systematic approach on SLC research and should be considered when studying disease processes or novel potential drug targets.